2011
DOI: 10.1007/s00464-011-1682-5
|View full text |Cite
|
Sign up to set email alerts
|

Ambulatory laparoscopic fundoplication for gastroesophageal reflux disease: a systematic review

Abstract: The data available to date in the literature, mostly of level 4 evidence, suggest that laparoscopic fundoplication for GERD appears to be safe and feasible in a day-surgery setting, subject to careful patient selection and surgeon expertise. Randomized control trials are urgently needed to better evaluate this promising care management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
10
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 26 publications
1
10
0
3
Order By: Relevance
“…More recently, reoperation incidence is reported to be resembling 5%[11]. A systematic review performed on elective LF documented an overall reoperation incidence approximating 0.6%[12]. In the nationwide study from Denmark, an incidence near to 5% of redo antireflux surgery was reported in 2589 patients[13].…”
Section: Introductionmentioning
confidence: 99%
“…More recently, reoperation incidence is reported to be resembling 5%[11]. A systematic review performed on elective LF documented an overall reoperation incidence approximating 0.6%[12]. In the nationwide study from Denmark, an incidence near to 5% of redo antireflux surgery was reported in 2589 patients[13].…”
Section: Introductionmentioning
confidence: 99%
“…A systematic review of ambulatory anti-reflux surgery described a range of 0–12.2% with an extrapolated mean of 3.5%. However, the authors comment that the evidence available for inclusion was poor quality [34]. A cohort study from the same group containing approximately 300 patients had a 30-day readmission rate of 8% [35], whilst a smaller cohort study of 113 patients who underwent day-case anti-reflux surgery in Sheffield had a rate of 3.5% [36].…”
Section: Discussionmentioning
confidence: 99%
“…Several single-centre case series have been published which have indicated that day-case LARS can be performed safely in selected patients, with similar post-operative morbidity and mortality to those who undergo an inpatient stay, although no randomised trials have been carried out [3438]. The one prospective study that examined cost found an estimated saving of 2367 Euros (assuming day of surgery admission as is standard UK practice) [35].…”
Section: Discussionmentioning
confidence: 99%
“…Nombre d'interventions chirurgicales digestives sont aujourd'hui pratiquées en routine en ambulatoire, parmi lesquelles la cholécystectomie [3], la cure de hernie [4], la fundoplicature [5] ou l'appendicectomie [6]. La voie d'abord mini-invasive pourrait permettre d'étendre la prise en charge ambulatoire à d'autres procédures plus lourdes.…”
Section: Introductionunclassified
“…indice de masse corporelle ; score ASA : score de l'American Society of Anesthesiologists.Tableau 2 Indications et types d'intervention.IndicationsKyste hépatique, n (Interventions Fenestration de kyste, n (%) 10 (50) Résection atypique, n (%) 10 (50) Laparoscopie par trocart unique, n (%) 1(5) cancer colorectal dans 4 cas (Tableau 2). *Selon des critères anatomiques.…”
unclassified